'Social media is their space': student and teacher use and perception of features of social media in language education. Issue 16 (10th December 2021) - Lambton-Howard, Daniel; Kiaer, Jieun; Kharrufa, Ahmed
ABSTRACT: Social media is seen as a powerful driver of change for language teaching and learning. Many studies have looked at the use and adoption rates of social media in language education, but studies that take a more fine-grained understanding of the differences between individual features of social media and how they are perceived by learners and teachers are rare. We present an analysis of the results of two workshops in a UK university that illustrate disparities between how individual features of social media are used generally, and how they are used for educational purposes between learners and teachers of languages. To understand the underlying perceptions of and attitudes towards features of social media we performed an inductive thematic analysis of discussion data generated at the workshops. From this we surface three themes: social media as distinct language type; navigating appropriateness; and prioritizing authentic communication flow. From these themes, we offer four design recommendations for practitioners and researchers who wish to incorporate social media in language teaching. These recommendations are: pay attention to specific features of social media and model authentic use; create learner-led and learner-owned spaces; create structured pathways to authentic social media use; and incorporate social media in assessment.